HOMESTAY AS A PILLAR OF COMMUNITY-BASED ECONOMY: A COMMUNITY EMPOWERMENT STUDY IN KANAGARIAN TABEK PANJANG - Hendri Azwar; Feri Ferdian; Pasaribu Pasaribu (Community Development Journal : Jurnal Pengabdian Masyarakat, 2025)
Nagari Tabek Panjang, located in Baso District, Agam Regency, is a village rich in tourism potential, encompassing natural, cultural, and artificial attractions. However, low tourist visitation remains a significant challenge. One contributing factor is the absence of derivative products from homestays that could serve as attractions to extend tourists' length of stay. Therefore, it is essential to develop homestays by utilizing local community houses and traditional houses near tourist attractions. This community service activity aims to facilitate the residents of Nagari Tabek Panjang in acquiring knowledge and skills to manage homestays and develop tourism packages. Consequently, it is expected that tourists will be encouraged to stay longer. Activities conducted include training on introducing homestays as part of Community-Based Tourism (CBT) and training on developing derivative homestay products. These outcomes are expected to support tourism development and enhance the local economy in Nagari Tabek Panjang.